Cooper pair dispersion relation in two dimensions - Adhikari, S. K.; Casas, M.; Puente, A.; Rigo, A.; Fortes, M.; Solis, M. A.; de Llano, M.; Valladares, A. A.; Rojo, O. (Elsevier B.V., 2000)
The Cooper pair binding energy vs. center-of-mass-momentum dispersion relation for Bose-Einstein condensation studies of superconductivity is found in two dimensions for a renormalized attractive delta interaction. It crosses over smoothly from a linear to a quadratic form as coupling varies from weak to strong.